Mao. 8 - Takahashi, Rumiko, 1957-; Garrity, Shaenon K. (Shōnen Sandē komikkusu., 2022)
"As Mao and company begin to uncover Yurako's true identity, another mystery lands on their doorstep--who or what is causing members of the Kagami family to commit shocking acts of violence? Unfortunately, our friends soon discover the truth in the old saying "No good deed goes unpunished." Then, when a puppet master gains control of Mao, no one is safe. Plus, Mao and Nanoka go on...a date?!"--Page [4] cover.